China's Revisionism Versus India's Status Quoism: Strategies and Counter-strategies of Rivals in Doklam Standoff. (June 2020) - Kumar, Suneel
Abstract: This article contends that China, as a part of its broader global agenda, is striving to recast the regional order in East Asia, South East Asia, and South Asia. Its revisionist moves and growing influence in South Asia are perceived by New Delhi as challenge to its national security and regional position thus forcing it to counter the Chinese moves and preserve the status quo ensuing into bilateral rivalry. Doklam standoff was an outcome of this bilateral rivalry between the two emerging Asian powers as Beijing attempted unilaterally to alter the prevailing territorial arrangement in the area of dispute and New Delhi counter-attempted to maintain the status quo. During the standoff, China projected itself as 'victim' of India's aggression while making provocative military deployments and threats of war against India. Opposite to this, India absorbed Beijing's pressure and defended its move in Doklam giving the logic of its 'security concerns' and 'special relationship' with Bhutan. New Delhi asked Beijing to resolve the dispute diplomatically while emphasizing on their troops' mutual withdrawal from the site of standoff.